Mekanisme Pemberhentian Presiden Republik Indonesia - Iskandar Iskandar (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The term impeachment of the president is not clearly written in the constitution. In the New Edition of the Big Indonesian Dictionary, it is stated that impeachment is putting down a position; abdicate the king. Impeachment is also an absorption language from Arabic which means demoted from office. It is defined by the term 'impeachment' in the constitutions of Western countries. The dismissal of the President and/or Vice President is carried out with the mechanism regulated in Articles 7A and 7B of the 1945 Constitution. Before the MPR dismisses the President and/or the Vice President, the appropriate mechanism must be followed. The President and/or Vice President may be impeached if they have violated the law in the form of treason against the state, corruption, bribery, other serious crimes, or disgraceful acts; and/or opinion that the President and/or vice president no longer meet the requirements as president and/or vice president.